2020
DOI: 10.1016/j.scienta.2019.05.004
|View full text |Cite
|
Sign up to set email alerts
|

I. Mineral nutrient profiles and relationships of ‘Honeycrisp’ grown on a genetically diverse set of rootstocks under Western New York climatic conditions

Abstract: We measured mineral nutrient concentrations in leaves, fruit flesh and fruit peel from field grown apple trees grown on a genetically diverse group of rootstocks from the fifth leaf through the eigth leaf (2014)(2015)(2016)(2017) and identified relationships between nutrients in leaves and fruit of 'Honeycrisp' apple. We also evaluated the constancy of rootstock influence on scion nutrient profiles over the four years. Boron concentration was consistent in different seasons, with rootstocks M.9 (several clones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 54 publications
(43 reference statements)
1
15
0
Order By: Relevance
“…The content of S was positively correlated to K, Mg, and P content ( r = 0.647; r = 0.657; and r = 0.628, respectively). Similar results for correlation between Mg and S, K and S, and between S and P, were determined in “Honeycrisp” apples grown on different rootstocks in Champlain valley in New York and Western New York climatic conditions ( 62 , 63 ).…”
Section: Resultssupporting
confidence: 72%
“…The content of S was positively correlated to K, Mg, and P content ( r = 0.647; r = 0.657; and r = 0.628, respectively). Similar results for correlation between Mg and S, K and S, and between S and P, were determined in “Honeycrisp” apples grown on different rootstocks in Champlain valley in New York and Western New York climatic conditions ( 62 , 63 ).…”
Section: Resultssupporting
confidence: 72%
“…Most are related to the mineral nutrition and bitter pit incidence relationship. Two studies reported a clear, positive relationship between potassium-to-calcium ratio and bitter pit incidence [ 17 , 18 ] (Valverdi et al, 2021; Fazio et al, 2020). However, mineral content is not the only criterion for the occurrence of bitter pit and does not always explain the presence or absence of symptoms in a particular orchard [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…They reported that morphological and biochemical parameters such as lower plant height, lower mineral nutrient concentrations [phosphorous (P), potassium (K), magnesium (Mg), zinc (Zn), and copper (Cu)], specific hormonal ratios and higher starch content can be considered as preferable indices for the selection of dwarfing apple rootstocks and these characteristics were found in M.9 rootstock. Some dwarfing rootstocks including B.9, M.9, and M.26 were also categorized in the "low" category for boron (B) absorption and transfer to grafted scions such as 'Fuji' and 'Honeycrisp' over multiple years and field trials indicating a rootstock genotype specific influence on mineral nutrient level concentration in grafted scions (Fazio et al, 2015(Fazio et al, , 2020Reig et al, 2018). The report by Hayat et al (2019), to some extent, agrees with earlier reports where fruit quality attributes in the 'Stark Spur Golden Delicious' apple fruit on OAR-1 rootstock was superior to those on other rootstocks (Fallahi et al, 1985b), because of their lower nitrogen concentrations (Fallahi et al, 1984).…”
mentioning
confidence: 99%